Математическая модель и подходы к решению обратной задачи при накоплении сейсмических сигналов в активном мониторинге - Мостовой, С.В.; Мостовой, В.С.; Осадчук, А.Е. (Центр менеджменту та маркетингу в галузі наук про Землю ІГН НАН України, 2008)
One actual problem in the field of quantitative seismology is lack of perfect technologies to carry out remote observations over a mechanical stress field in the Earth’s crust. Seismic monitoring is regarded as an efficient technology for ground seismological observations. Its productivity has been repeatedly confirmed by practice, and it is widely applied nowadays to the operative control of a condition of both natural and man-made complexes such as: geological faults, mines, dams, excavated oil and gas deposits, etc. Among various versions of seismic monitoring technologies it is possible to discriminate an active monitoring by stream weak probing sound signals, being comparable with the natural background due to energy properties. Contributory features of this type of monitoring are taken into consideration, being connected with fluctuating parameters of probing sound signals in the mode of their accumulation and subsequent processing. The simulated numerical example illustrates main aspects of proposed mathematical model. To avoid an imperfect approach to solving, for example, integrated equations of convolution, it is important to construct procedures based on some additional information specific model, which could lead to successful results and stability. These equations are a good model for a wide range of phenomena and well-known in geophysics. Such approach is offered in the form of estimation of these parameters by the chosen criterion, based on a priori free parameters of the model.